Extranodal tuberculosis of the head and neck - Santosh Kumar Swain; Mahesh Chandra Sahu; Manash Ranjan Baisakh; Anwesha Banerjee (Apollo Medicine)
Extranodal tuberculosis (TB) of the head-and-neck area is a rare clinical entity and constitutes the less common type of extrapulmonary TB. It often creates challenges among head-and-neck physicians for its diagnosis and treatment. Extranodal TB is a rare clinical entity and has no specific clinical features. It is often a differential diagnosis of head-and-neck malignancies, chronic infective or noninfective ulcers. Early diagnosis and its treatment may avoid complications and needless major surgery. The purpose of this review article is to discuss the epidemiology, pathophysiology, clinical presentations, diagnostic challenges, and treatment of the extranodal TB of the head-and-neck area.